3(x+6)=4(x-13)

Simple and best practice solution for 3(x+6)=4(x-13) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+6)=4(x-13) equation:



3(x+6)=4(x-13)
We move all terms to the left:
3(x+6)-(4(x-13))=0
We multiply parentheses
3x-(4(x-13))+18=0
We calculate terms in parentheses: -(4(x-13)), so:
4(x-13)
We multiply parentheses
4x-52
Back to the equation:
-(4x-52)
We get rid of parentheses
3x-4x+52+18=0
We add all the numbers together, and all the variables
-1x+70=0
We move all terms containing x to the left, all other terms to the right
-x=-70
x=-70/-1
x=+70

See similar equations:

| z/5+80=88 | | -4(2x+3)=-(6x-20) | | 28.24=6g+3.58 | | -7/8=-3/4x+1/3 | | X=32m2 | | 5x-1+7-13+6x-4=13 | | 6u−36=-42 | | 9+4n=15-n | | 2r-18=-2 | | 2x-7=137-2x | | h+5.7=-5.7 | | 6x+6=-150-7x | | 5x-16+2x=7x-2 | | 3q-6(q-8)=42 | | 2n+5+6=1+7n | | 5(-6f)+13)=35 | | 1.5x+2.5-1.5=0.5x+3 | | h+26=839 | | -3+-2h=1 | | −25=k−17 | | 4-2(3x-5)=-40 | | 13-x=3+7x | | -4b+8+6b+2=b+1+6 | | 10x+3=2(5x)+3 | | A.10b+8b+9−18b+3=5+6b−2b−12+7 | | 2.2x=-8.8 | | 2x+24=x+19 | | 4x+6=9-4x | | 2x-7=-7+7x | | x+6-2=-15 | | 10-15p=-30+135p | | .42b-8.3+9.14b=-5.91 |

Equations solver categories